Principles and Pedagogies in Jewish Education - Chazan, Barry (Springer Nature, 2022)
This book is aimed at improving contemporary educational practice by rooting it in clear analytical thinking. The book utilizes the analytic approach to philosophy of education to elucidate the meaning of the terms (3z(Beducation,(3y z(Bmoral education,(3y z(Bindoctrination,(3y z(Bcontemporary American Jewish education,$1 (3z(Binformal Jewish education,(3y z(Bthe Israel experience,(3y (Band (3z(BIsrael education.(3y (BThe final chapter of the book presents an educator$1 (Bs credo for twenty-first Jewish education and general education. This is an open access book.s
English
Keywords: Philosophy & theory of education; Educational strategies & policy; Child & developmental psychology; Moral Education; Faith-based education; experiential learning; educational philosophy; indoctrination; Open Access